Resilience and mental health problems in children and adolescents who have been victims of violence - Natália Amaral Hildebrand; Eloisa Helena Rubello Valler Celeri; André Moreno Morcillo; Maria de Lurdes Zanolli (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To understand the process of resilience (social support and resources of the family environment) and the chance of mental health problems in children and adolescents (9-16 years) who have been victims of domestic violence, assisted in specialized services (Group 1 - G1) and in school services without reports of domestic violence (Group 2 - G2). METHODS: Various semi-structured instruments were applied to the pairs (guardian and child or adolescent): the Strengths and Difficulties Questionnaire (SDQ); the Resiliency Scales for Children and Adolescents (RSCA), including Scale I (SI - sense of control), Scale II (SII - relationship skills) and Scale III (SIII - emotional reactivity); the Social Support Appraisals; the Home Environment Resources Scale and a questionnaire created by the authors to characterize the population. RESULTS: There was no difference in the prevalence of resilience between G1 and G2. Children and adolescents of both groups had a higher chance of low resilience in the absence of perception of social support from the teacher (SI; SIII) and other people in the community (SI; SII). Girls had higher chance of low resilience (SIII). The establishment of routine or rules in the lives of the children and adolescents facilitated the development of resilience (SIII). In G1, the prevalence of mental health problems was 65% for the self-application version of the SDQ for children and adolescents (SDQ/CA) and 54% for the version answered by the guardians (SDQ/G). In G2, it was 33% for SDQ/CA and 37.9% for SDQ/G. Domestic violence against children and adolescents was a risk factor for the development of mental disorders (SDQ/G). Subjects with low resilience (SI) had a higher chance of developing mental health problems (SDQ/CA). Despite originating from the same regions, the groups had socioeconomic differences, which showed no relationship with resilience. CONCLUSIONS: The quality and perception of social support and resources present in the home environment may have facilitated the development of resilience in the studied children and adolescents. Violence may have increased the chance of mental health problems, domestic violence being an aggravating factor. There is need for research on aspects that predict resilience and investment in intervention strategies for this population, as a way to promote mental health.